Analisis Makna Lafadz Sulthan dalam Al-Qur’an: Studi Perspektif Semantik / Analysis of the Meaning of Lafadz Sulthan in the Qur’an from the Perspective of Semantic Studies - Linur, Rahmat; Ritonga, Mahyudin Ritonga; Julhadi, Julhadi (Diwan: Jurnal Bahasa dan Sastra Arab, 2022)
The term “Sulthan” is one of the Musytarak words (words with several meanings) found in the Qur’an. The term "Sulthan" has a wide range of connotations that must be understood since it does not always refer to a leader; it may also refer to a dispute or other meanings depending on the context of the phrase. Following that, the purpose of this research is to determine the meaning of the word "Sulthan" using a semantic method. A qualitative approach was taken. The Qur’an, Mu’jam al-Mufahras li alfaz Al-Qur’an, Tafsir textbooks (commentary books), pertinent publications, and articles with a substantial link to the study’s topic were all used as data sources. Reading served as the primary and secondary data sources for data gathering. The Qur’an was thoroughly read to find the word "Sulthan." In the meantime, Mu’jam al-Mufahras li alfaz Al-Qur’an, tafsir textbooks (commentary books), relevant books, and articles were used to discover the meaning of "Sulthan" based on the notions of expert interpreters (Mufassir) and credible linguists. Henceforth, the results were examined and validated using a comparison approach, specifically comparing the thoughts of experts (Mufassir and linguists) on the definition of "Sulthan." Concerning a semantic analysis comparison of expert thoughts, the research revealed the true meaning of the word "Sulthan." The results reveal that the term "Sulthan" appears in 37 verses of the Qur’an. Therefore, the definition of "Sulthan" in 37 verses of the Qur’an can be divided into four meaning sections: 1) Sulthan is an argument or evidence; 2) Sulthan is a miracle; 3) Sulthan is power or capabilities; and 4) Sulthan is leadership. This analysis has limitations in terms of in-depth investigation based on the opinions of certain specialists. As an outcome, it is recommended that the next researcher in the next study accomplishes it. مستلخص كلمة "سلطان" هي واحدة من عدد الكلمات الواردة في المشترك التي توجد في القرآن. تُفهم الأنواع المختلفة من معاني كلمة "سلطان" بشكل صحيح، لأن هذه الكلمة لا تعني دائمًا بمعنى القائد، مع وجود الدلالة في الجملة المستخدمة، وتعني الكلمة أحيانًا بمعنى الحجة أو غيره. لذلك يهدف هذا البحث إلى الكشف عن معنى كلمة "سلطان" باستخدام المنهج الدلالي. الطريقة المستخدمة في هذا البحث هي الطريقة النوعية. ومصادر البيانات المستخدمة هي القرآن، ومعجم المفهرس لألفاظ القرآن، وكتب التفسير، والكتب، والمقالات ذات الصلة. وتم جمع البيانات بعناية فائقة في قراءة المصادر - المصادر الأولية والثانوية. يُقرأ القرآن كمصدر رئيسي للعثور على كلمة "سلطان"، بينما يُقرأ معجم المفهرس لألفاظ القرآن وكتب التفسير والكتب والمقالات ذات الصلة للعثور على معنى كلمة "سلطان" عند علماء التفسير وعلماء اللغة. تم تحليل البيانات واستندت إلى تقنية مقارنة رأي الخبراء فيما يتعلق بمعنى كلمة "سلطان"، وبعد مقارنة تلك آراء تقرر المعنى الحقيقي لكلمة سلطان وفقا بالتحليل الدلالي. بناءً على البحث توجد النتائج، أن استخدام كلمة "سلطان" في القرآن وارد في سبعة وثلاثين آية. وفقًا للتحليل الذي تم إجراؤه، يمكن تصنيف معنى كلمة "سلطان" الواردة في سبعة وثلاثين آية إلى أربع مجموعات من المعاني، وهي كلمة "سلطان" بمعنى الحجة أو الدليل، و كلمة "سلطان" بمعنى المعجزة، وكلمة "سلطان" بمعنى القوة أو القدرة، وكلمة "سلطان بمعنى السلطة أو السلطة. يقتصر هذا البحث على أن معنى كلمة "سلطان" لم يتم تحليله بعمق بناءً على رأي بعض الخبراء، ويمكن أن يكون هذا الجانب من عمل المزيد من الباحثين بعده. الكلمات المفتاحية: سلطان؛ المشترك اللفظي؛ دلالة